2020
DOI: 10.2147/dmso.s237700
|View full text |Cite
|
Sign up to set email alerts
|

<p>Common and Unique Factors and the Bidirectional Relationship Between Chronic Kidney Disease and Nonalcoholic Fatty Liver in Type 2 Diabetes Patients</p>

Abstract: This study aimed to investigate the common and unique risk factors and bidirectional relationship between chronic kidney disease (CKD) and nonalcoholic fatty liver disease (NAFLD) in patients with type 2 diabetes mellitus (T2DM). Patients and Methods: This was a cross-sectional study of patients with T2DM enrolled in a disease management program at two specialized diabetes outpatient clinics. Common and unique risk factors for CKD and NAFLD were examined using structural equation models (SEMs). SEMs were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 45 publications
2
15
0
2
Order By: Relevance
“…NAFLD and CKD share similar pathological mechanisms, therefore they are speculated to have some links. The aforementioned mechanisms included the role of obesity, insulin resistance, the reninangiotensin system, and dysregulation of glucose metabolism and lipogenesis in the development of both disorders [17,44,45]. In this study, in line with the concept that NAFLD is the hepatic manifestation of the metabolic syndrome, the presence of NAFLD is associated with obesity and components of metabolic syndrome.…”
Section: Discussionsupporting
confidence: 63%
“…NAFLD and CKD share similar pathological mechanisms, therefore they are speculated to have some links. The aforementioned mechanisms included the role of obesity, insulin resistance, the reninangiotensin system, and dysregulation of glucose metabolism and lipogenesis in the development of both disorders [17,44,45]. In this study, in line with the concept that NAFLD is the hepatic manifestation of the metabolic syndrome, the presence of NAFLD is associated with obesity and components of metabolic syndrome.…”
Section: Discussionsupporting
confidence: 63%
“…Lu et al reported that serum hepassocin concentrations are gradually increased in diabetic patients with NAFLD, and suggested that increased hepassocin levels might have clinical implications and could play a role as a biomarker for diabetes and NAFLD 25 . Our recent study showed that a bidirectional relationship existed between CKD and NAFLD in patients with type 2 diabetes mellitus 14 . Consistent with these findings, it was found in the present study that patients in the high hepassocin group were associated with increased rates of fatty liver and decreased eGFR.…”
Section: Discussionmentioning
confidence: 96%
“…In view of the fact that hepassocin causes hepatic steatosis and induces IR, and because CKD has a clear association with both hepatic steatosis and type 2 diabetes 14 , 15 , the authors postulated that hepassocin might be the link between these diseases. The aim of the present study was to clarify the clinical significance of circulating hepassocin levels in the context of fatty liver and renal function status.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating data now suggest that the association between NAFLD and risk of prevalent CKD may be even bidirectional [145] . For example, in an observational study enrolling approximately 2,000 Taiwanese patients with T2DM, Lee et al [73] confirmed an independent association between imaging-diagnosed NAFLD and CKD (adjusted odds ratio 1.59, 95% confidence interval 1.12-2.25). Interestingly, when the authors performed a structural equation model analysis to test the effects of NAFLD on CKD and the potential role of CKD on NAFLD, they found the existence of a bidirectional relationship between NAFLD and CKD [73] .…”
Section: Increased Risk Of Ckd In Nafld Patients With T2dmmentioning
confidence: 97%
“…Indeed, the observational studies involving European or USA patients have reported a prevalence of NAFLD higher than that observed in the studies involving Asian patients. Additional factors that might explain these findings are different lifestyles (i.e., sedentary, physical inactivity), diets (i.e., high caloric diets, especially in the form of carbohydrates and Hamid et al [72] 203 Pakistani patients with T2DM diagnosed during the last 6 months were enrolled Mean age 53 years, 51% males Prevalence of NAFLD on US was 71.9% Lee et al [73] 1,992 Taiwanese patients with T2DM who participated in a disease management program at two specialized diabetes outpatient clinics. Mean age 66 years, mean BMI 26 kg/m 2 , 34% males Prevalence of NAFLD on US was 55.9%…”
Section: Prevalence Of Nafld In Patients With Diabetes Mellitusmentioning
confidence: 99%